Gender and Inequality: Austerity and Alternatives - Diane Perrons (Intereconomics, 2017)
Gender equality policies aim to increase women's participation in the market economy, but they do not always recognise that market societies reproduce inequalities at micro and macro levels. At the micro level, labour markets are gendered institutions, and at the macro level, austerity policies have inherent biases and negative impacts that fall disproportionately on women.
Keywords: 330